Audit Secara Prospektif terhadap Antimicrobial Stewardship Program pada Pasien Kanker Payudara di RSUP Dr. M. Djamil Padang - Yelly Oktavia Sari; Rustini Rustini; Diva Diana; Telsa Dwiana Hapsari (Jurnal Sains Farmasi & Klinis, 2017)
Surgery has been used as part of the treatment of breast cancer, but surgery has a potential risk of infection due to the effect of normal flora on the body and air in the ward environment. The decrease of antibiotics effectiveness is caused by bacterial resistance to antibiotics. The purpose of this study was to find out the pattern of bacteria, antibiotic sensitivity patterns and patterns of antibiotic use among breast cancer patients in the surgery ward Hospital M. Djamil Padang. An observational prospective study design was performed in this study, whereby data was collected from the medical records of patients admitted to the surgery wards of Hospital Dr. M. Djamil Padang from April – September 2017. Results showed the bacterial identification in patients were Staphylococcus aureus and Klebsiella sp. while from the air were found Staphylococcus aureus, Staphylococcus epidermidis and Klebsiella sp. Based on the sensitivity pattern on surgical wounds during April-May 2017 reported amoxicillin/ clavulanic acid and meropenem were good (>80%) while on August-September 2017 was meropenem. Airborne sensitivity patterns result during April-May 2017 were not found, while on August-September 2017 gentamicin, ciprofloxacin and meropenem were good (>80%). Among 32 patients admitted during study period only 7 patients who fulfilled the inclusion criteria. The most common antibiotic used was ceftriaxone 7 (77,8%). The evaluation of the rationale use of antibiotics were 6 (66.7%) appropriate medication, 9 (100%) appropriate dosage, 7 (77.8%) appropriate time duration, 9 (100%) appropriate route, 7 (100%) appropriate patient, 4 (45,1%) appropriate indication and potentially drug interaction 1 (14,28%) as a minor potency.